The Practical Significance of Developing Students’ Intellectual and Creative Abilities through English Language Teaching - Haydarova , Nozigul (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article describes the goals and objectives of experimental work on improving the intellectual and creative abilities of students based on the English language.